Suspended sediment and faecal contamination in a stormflow plume from the Hutt River in Wellington Harbour, New Zealand. Issue 3 (3rd July 2022) - Gall, Mark P.; Davies-Colley, Rob; Milne, Juliet; Stott, Rebecca
ABSTRACT: Muddy, faecally-contaminated river flood plumes in coastal waters are a hazard to contact recreation and bivalve shellfish consumption but are difficult to study, being episodic and transient. We used a new underway flow-through sampler in a small, fast boat, to map a flood plume within Wellington Harbour, while simultaneously sampling water in the Hutt River inflow. Faecal contamination (indexed by E.coli) correlated with flow, salinity, coloured dissolved organic matter, total suspended solids (TSS) and water clarity (light beam attenuation and visual clarity). The freshwater content of the plume agreed well with time-integrated river discharge. Despite the relatively short time-scale (<12 h) of the event, a 21% loss of TSS (particle flocculation and settling), and 30% loss in E. coli (suggesting some die-off) occurred in the plume compared to river loads. E. coli relative to TSS varied up to two orders of magnitude over a year of river flood sampling. A rapid survey of plumes combined with long-term river observations is expected to augment monitoring and inform the extension of remote sensing and modelling efforts to faecal contamination of New Zealand coastal waters.